Close Readers : Humanism and Sodomy in Early Modern England. - Stewart, Alan, 1967- (Princeton legacy library., 2014)
Humanism, in both its rhetoric and practice, attempted to transform the relationships between men that constituted the fabric of early modern society. So argues Alan Stewart in this ground-breaking investigation into the impact of humanism in sixteenth-century England. Here the author shows that by valorizing textual skills over martial prowess, humanism provided a new means of upward mobility for the lowborn but humanistically trained scholar: he could move into a highly intimate place in a nobleman's household that was previously not open to him. Because of its novelty and secrecy, the in.